Concept and structure of the special forces of operative-search activity - V. M. Davydiuk (Law and Safety)
Some essential aspects of the concept of “special forces of operative and search activity” have been revealed, as well as their structural elements have been outlined. Information to clarify the content of the concept of “special forces of operative and search activity” and its certain components has been systematized. The author has studied the interpretation of the relevant components of this term in the literature, as well as taking into account the practical aspects of the organization of operative and search activities. The relevant international experience has been analyzed. Attention has been paid to the fact that only those persons, who cooperate with law enforcement agencies on a confidential basis are logically treated as special forces of operative and search activity. Some aspects of the application of special forces of operative and search activity have been revealed. Emphasis has been placed on ensuring secrecy and confidentiality in the use of special forces of operative and search activity. It has been emphasized that in case of the fulfillment of the tasks of operative and search activity such forces get a special attitude from the law enforcement agencies. The author has attempted to classify such forces, and has defined the attributes relevant to them. Based on the research, the definition of special forces of operative and search activity has been provided – it is a separate category of forces of operative and search activity, which does not belong to the subjects of operative and search activity, but indirectly and on a confidential basis promotes the fulfillment of tasks of operative and search activity and criminal process. The author has substantiated that disclosing party and anonymous author, who provide information on a confidential basis, belong to special forces of operative and search activity.